2021
DOI: 10.1007/s00109-021-02124-9
|View full text |Cite|
|
Sign up to set email alerts
|

The recurrent missense mutation p.(Arg367Trp) in YARS1 causes a distinct neurodevelopmental phenotype

Abstract: Pathogenic variants in aminoacyl-tRNA synthetases (ARS1) cause a diverse spectrum of autosomal recessive disorders. Tyrosyl tRNA synthetase (TyrRS) is encoded by YARS1 (cytosolic, OMIM*603,623) and is responsible of coupling tyrosine to its specific tRNA. Next to the enzymatic domain, TyrRS has two additional functional domains (N-Terminal TyrRSMini and C-terminal EMAP-II-like domain) which confer cytokine-like functions. Mutations in YARS1 have been associated with autosomal-dominant Charcot-Marie-Tooth (CMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…Our case stands out due to the identification of the YARS1 p.Arg367Trp variant in the patient's father. This particular variant has been previously documented by Averdunk et al ( 9 ) as recurrently homozygous in their study of 12 cases, with 8% (1/12) exhibiting mild hearing impairment ( 9 ) Interestingly, our patient failed both the initial and subsequent newborn hearing screens in the left ear. Meanwhile, the patient's father, now 48 years old, encountered adult-onset hearing loss, necessitating the use of hearing aids.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our case stands out due to the identification of the YARS1 p.Arg367Trp variant in the patient's father. This particular variant has been previously documented by Averdunk et al ( 9 ) as recurrently homozygous in their study of 12 cases, with 8% (1/12) exhibiting mild hearing impairment ( 9 ) Interestingly, our patient failed both the initial and subsequent newborn hearing screens in the left ear. Meanwhile, the patient's father, now 48 years old, encountered adult-onset hearing loss, necessitating the use of hearing aids.…”
Section: Discussionsupporting
confidence: 74%
“…These children presented with a broader spectrum of symptoms, including brain dysmyelination, nystagmus, exocrine pancreatic insufficiency, renal dysfunction, hypoglycemia, anemia, intermittent proteinuria, and recurrent bloodstream infections ( 16 ). Averdunk et al ( 9 ) identified 12 individuals from six families with a recurrent homozygous missense variant c.1099C > T, p.(Arg367Trp) in YARS1, who also exhibited microcephaly, short stature, ataxia, microcytic anemia, and hypothyroidism. A subset of individuals additionally suffered from hearing impairment, gastroesophageal reflux, vomiting, and pulmonary disease ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, two YARS1 subunits must form an asymmetric homodimeric complex with two tyrosyl tRNAs for the aminoacylation reaction to occur (J Ward and Fersht, 1988). Previously, homozygosity or compound heterozygosity for loss-of-function YARS1 variants have been associated with severe, early-onset, multisystem disease, with phenotypes including liver dysfunction, developmental delay, brain anomalies, and sensorineural hearing loss (Averdunk et al, 2021;Estève et al, 2021;Nowaczyk et al, 2017;Williams et al, 2019). Furthermore, heterozygosity for missense variants or a small, in-frame deletion in YARS1 have been associated with dominant intermediate Charcot-Marie-Tooth neuropathy, type C (DI-CMTC; MIM #608323), which is characterized by progressive weakness and sensory loss in the distal upper and lower extremities, with intermediate motor nerve conduction velocities between 25 and 45 m/s (Hyun et al, 2013;Jordanova et al, 2003Jordanova et al, , 2006.…”
Section: Case Presentationmentioning
confidence: 99%